Tension/compression asymmetry in additive manufactured face centered cubic high entropy alloy. (1st March 2017) - Joseph, Jithin; Stanford, Nicole; Hodgson, Peter; Fabijanic, Daniel Mark
Abstract: The high entropy alloy, Al0.3 CoCrFeNi, has been fabricated by direct laser fabrication and its deformation behaviour studied. This alloy exhibited significant tension/compression asymmetry in its work hardening rate and ductility. The exceptionally high work hardening in compression has been attributed to profuse mechanical twinning which has been exacerbated by a strong texture in the as-cast material. The tensile deformed material did not exhibit any mechanical twinning, deformed exclusively by slip, and therefore showed minimal work hardening and poor ductility. The critical resolved shear stress for twinning of the alloy was found to be approximately 240 MPa. Graphical abstract: